Dynamic risk and sexual offending: the conundrum of assessment. Issue 1 (22nd January 2016) - Casey, Sharon
ABSTRACT: The potential to reduce sexual victimisation, promote community safety, and decrease incarceration costs has resulted in considerable progress in terms of how we understand and predict sexual recidivism. And yet, the past decade has seen a degree of fragmentation emerge as research attention has shifted away from relative risk prediction (with its focus on static risk factors) to the identification of factors capable of reducing risk through intervention (i.e. dynamic risk). Although static and dynamic risk are often treated as orthogonal constructs [Beech, A. R., & Craig, L. A. (2012). The current status of static and dynamic factors in sexual offender risk assessment. Journal of Aggression, Conflict and Peace Research, 4 (4), 169–185. doi:10.1108/17596591211270671], there are arguments to support a claim that the two are in fact functionally related [see Ward, T. (2015). Dynamic risk factors: Scientific kinds or predictive constructs. Psychology, Crime & Law (in 22(01–02), 2–16); Ward, T., & Beech, A. R. (2015). Dynamic risk factors: A theoretical dead-end? Psychology, Crime & Law, 21 (2), 100–113. This discussion clearly affects how we assess dynamic risk. This review considered several commonly used methods of assessment and the evidence offered for their predictive accuracy. Of note were differences in the predictive accuracy of single psychometric measures versus composite scores of dynamic risk domains and the conventions used for establishing effect sizes for risk assessment tools.